Political economy and instruments of environmental politics - Schneider, Friedrich; Kollmann, Andrea, 1980-; Reichl, Johannes, 1979- (CESifo seminar series., 2015)
Economists have long argued that market-based instruments such as, environmental taxes, and emission trading systems, are the superior way to offset the negative externalities of any kind of economic activities. Yet, whether the effects of using these instruments are sufficient, whether they are actually used efficiently, and especially which factors influence their effectiveness is subject to a lively debate. It is the ultimate task of research to identify existing barriers among economic agents so as to gain valuable insight into how to overcome them. There still is much work to be done when it comes to evaluating the effectiveness of policy instruments with regard to the achievement of environmental targets. This work examines this topic.